2014
DOI: 10.1182/blood-2014-03-564997
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and risk criteria for HSCT-associated thrombotic microangiopathy: a study in children and young adults

Abstract: • Proteinuria and elevated markers of complement activation at TMA diagnosis are associated with poor outcome.• Clinical interventions should be considered in HSCT patients with these high-risk features at the time TMA is diagnosed.Transplant-associated thrombotic microangiopathy (TMA) leads to generalized endothelial dysfunction that can progress to multiorgan injury, and severe cases are associated with poor outcomes after hematopoietic stem cell transplantation (HSCT). Identifying patients at highest risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
443
5
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 341 publications
(495 citation statements)
references
References 43 publications
7
443
5
5
Order By: Relevance
“…7,8,13,14 In the first prospective study of TMA in pediatric patients, incidence was reported to be as high as 35% and presence of TMA associated with higher non-relapse mortality than in patients without TMA. 1 Jodele et al 15 proposed that TMA is characterized by multi-organ endothelial injury affecting kidneys, gut, serosal surfaces, heart, skin and lungs, all in the setting of hemolytic anemia and thrombocytopenia. Martinez et al 16 studied 221 consecutive patients and noted a 31% incidence of TMA at 100 days post HCT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,13,14 In the first prospective study of TMA in pediatric patients, incidence was reported to be as high as 35% and presence of TMA associated with higher non-relapse mortality than in patients without TMA. 1 Jodele et al 15 proposed that TMA is characterized by multi-organ endothelial injury affecting kidneys, gut, serosal surfaces, heart, skin and lungs, all in the setting of hemolytic anemia and thrombocytopenia. Martinez et al 16 studied 221 consecutive patients and noted a 31% incidence of TMA at 100 days post HCT.…”
mentioning
confidence: 99%
“…[1][2][3] These conditions share a common end point of microthrombotic vascular endothelial cell injury, but with differing underlying pathophysiologic mechanisms. The TMA in TTP is related to severely deficient ADAMTS13 activity and the resulting ultra-large Von Willebrand factor multimers that aggregate platelets in conditions of high shear forces.…”
mentioning
confidence: 99%
“…9,26 In 2014, an international panel suggested updated diagnostic guidelines. 1, 31 In our study, the adaptation of the proposed criteria was limited by the lack of serum complement C5b-9 measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney is one of the most critical organs affected by this disease, emphasizing the importance of monitoring renal function via SCr or estimated glomerular filtration rate. Jodele et al 24 showed that in the early post-transplant phase, screening for proteinuria and monitoring urine protein/creatinine ratios can offer diagnostic and prognostic value for patients who are likely to develop TMA after transplantation. This study demonstrated the importance of close monitoring of urinary markers of kidney function, in addition to serum markers.…”
Section: Incidence Of Post-bmt Tmamentioning
confidence: 99%